Not all shocks are created equal: Assessing heterogeneity in the bank lending channel - Laura Blattner; Luísa A. Farinha; Gil Nogueira (European Central Bank (ECB), 2021)
We provide evidence that the strength of the bank lending channel varies considerably across three major events in the European sovereign debt crisis the Greek debt restructuring (PSI), outright monetary transactions (OMT), and quantitative easing (QE). We study how lending responds to each shock using detailed bank, firm, and household data from Portugal, a country that was directly exposed to the three events. While the price of sovereign debt securities increased in all three events, banks reduced sovereign debt holdings and realized accumulated capital gains only after QE. As a result, lending to final borrowers reacted more strongly to QE than to the PSI or OMT events. Our results suggest that asset purchases were more effective than signalling events at stimulating the bank lending channel.
Keywords: E52; E58; G18; G21; 330; asset purchases; bank lending channel; OMT; PSI; QE